KARAKTERISTIK TEKS CERPEN KARYA SISWA KELAS XI SMA NEGERI 11 PADANG - Martiana, Nita; Thahar, Harris Effendi (Universitas Negeri Padang, 2019)
ABSTRACT The purpose of this study is to describe (1) the characteristics of the short story text structure of class XI MIPA 4 SMAN 11 Padang and (2) the characteristic of the short story text elements by class XI MIPA 4 SMAN 11 Padang. Theories related to this research there are four theories, namely (a) understanding of short story text, (b) short story text structure, (c) elements in short story text, and (d) short story text style. The type of research used is qualitative research using descriptive methods. The data of this study are the results of the writing of the students of class XI MIPA 4 SMAN 11 Padang in the form of short stories totaling 33 short stories. The technique for validating the data used is a thick description. Data were analyzed using simple statistical descriptive techniques and qualitative analysis using formats. Based on the results of the study can be concluded,first, short story text by students of class XI MIPA 4 SMAN 11 Padang are more dominantly built on five structures, namely abstract, orientation, complications, evaluation, and resolution. It can be interpreted that the short story text by students of class XI MIPA 4 SMAN 11 Padang is not complex text structures. Second, short story text by students of class XI MIPA 4 SMAN 11 Padang dominantly using advanced plot. Third, short story text by students of class XI MIPA 4 SMAN 11 Padang then to use three types of language styles, namely hyperbolic style, personification, and simile. Kata kunci : Karakteristik, teks cerpen